Sclerotinia rot of brinjal and its host range in West Bengal (The Journal of Plant Protection Sciences, 2024)
In India, brinjal is the 4th most important  vegetable grown after potato, onion and to mato. According to an estimate about 1.4 mil lion small and marginal farmers in India grow  brinjal crop, which provide regular and steady  income to them (2). West Bengal has the lion  share in brinjal production (29.1%) in India,  occupying the highest in acreage and produc tion of brinjal among the states. A major  group of farmers are involved in brinjal culti vation for their income generation throughout  West Bengal. Presently cultivated area of  brinjal in West Bengal is 158.44 thousand ha  with a production and productivity of 2870.60  thousand tones and 18.11 ton/ha (Economic  Review, 2010-11, Govt. of West Bengal).  Wilting or death of brinjal plant is the major  constraint in brinjal cultivation.
Keywords: chlorampheni; symptoms; brinjal culti vation; Bengal